Tradition critical study of 1 Chronicles 21 - Geyser-Fouché, Ananda (HTS teologiese studies, 2021)
The purpose of this article was to highlight the importance of tradition criticism as a significant aspect of the exegetical study of any Old Testament text. Different traditions existed in ancient Israel, and the Chronicler emphasised or underemphasised some of these in 1 Chronicles 21. The above-mentioned practices highlight the theology and ideology that the Chronicler wanted to promote. The Chronicler emphasised certain traditions and underemphasised others in such a way that both the theology and ideology of the Jerusalem Temple stood out. The Jerusalem Temple represented the Chronicler’s theology and his image of God – which was that Yahweh is only to be worshipped in the Jerusalem Temple, that he has chosen the site as the place for worship and that he is dwelling there. The findings of this research caution against reading and understanding a text outside its unique historical context. This is because the Old Testament does not have a central theme or one theology.Contribution: This article contributes to the focus in HTS Teologiese Studies/Theological Studies with regard to the notion ‘historical thought’, covering textual and hermeneutical studies as expressed in the Hebrew Scriptures. The hermeneutical method of tradition criticism is applied in this article, forming part of the scope of this journal to embrace critical textual readings.